Casearia seethalakshmiae (Samydoideae, Salicaceae), a new species from Palakkad Gap, Kerala (India) - Ambika, Viswanathanpillai; Sojan, Jose; Suresh, Veerankutty (Phytotaxa, 2022)
Casearia seethalakshmiae, a new species from India, is described and compared with the three other currently accepted Indian species namely C. graveolens, C. glomerata, and C. bourdillonii. The new species belongs to the Casearia sect. Casearia, and is confined to Palakkad, Kerala. Detailed description, distribution, phenology, photographs and a key to the species of Indian Casearia are provided.